THE EFFECT OF CHICKEN MANURE TO GROWTH AND THE YIELD OF HIGH POTENCIAL RICES USING SRI METHOD - Nurjani, Putri Hermawati Mulyadi Safwan (Fakultas Pertanian Universitas Tanjungpura, 2019)
ABSTRACT The research aims to know the effect of manure and variety to both growth and rice